Occupations and the risk of head and neck cancer: a pooled analysis of the International Head and Neck Cancer Epidemiology (INHANCE) consortium - Khetan, Prerna; Ramroth, Heribert; Brenner, Hermann (Journal of occupational and environmental medicine, 2019)
OBJECTIVE: To investigate the associations between head and neck cancer (HNC) risk and occupations. - METHODS: We harmonized data on occupations in a pooled analysis of 8839 HNC cases and 13,730 controls in International Head and Neck Cancer Epidemiology (INHANCE) consortium. Logistic regression was used to estimate odds ratios (ORs) for associations of occupations and HNC risk. Population attributable fraction (PAF) for occupations was calculated using the formula PEC×(OR-1)/OR. - RESULTS: Trend of increasing HNC risk was found with increasing duration of employment for many occupations, including cooks (OR=1.36; 95% confidence interval [CI] 1.09 to 1.68), cleaners (OR=1.38; 95% CI 1.13 to 1.69), painters (OR=1.82; 95% CI 1.42 to 2.35). The PAF for a priori occupations was 14.5% (95% CI 7.1% to 21.9%) for HNC. - CONCLUSIONS: We found associations between certain occupations and HNC risks, including for subsites, with a duration-response relationship.